2012
DOI: 10.1080/00140139.2012.658086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of handicraft sitting postures on lower trunk muscle fatigue

Abstract: The purpose of this study was to assess trunk muscle fatigue in seated handicraft tasks using surface electromyography (sEMG) and visual analogue scale (VAS) ratings for trunk discomfort, and to assess the relationship of these responses. Twenty-three participants were randomly assigned to assumed crossed-leg and heel sitting postures for 30 min. Normalised median frequency (NMF) slopes for lumbar multifidus (LM) and internal oblique (IO) muscles and VAS ratings were recorded. Results revealed that the crossed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…Results revealed that NMF slope for the UT, CES, and SCM muscles were not different between shoulder taping and no taping conditions. Generally, muscle fatigue results from a task that requires sustained muscle contraction in static posture or repeated movements, and a steeper NMF slope of the muscle indicates more muscle fatigue [16] , [25] . Previous studies proposed a relationship between alterations of muscle activity and muscle fatigue [36] , [37] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results revealed that NMF slope for the UT, CES, and SCM muscles were not different between shoulder taping and no taping conditions. Generally, muscle fatigue results from a task that requires sustained muscle contraction in static posture or repeated movements, and a steeper NMF slope of the muscle indicates more muscle fatigue [16] , [25] . Previous studies proposed a relationship between alterations of muscle activity and muscle fatigue [36] , [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Neck discomfort was reported by the participants via texting on the touchscreen smartphone. Neck discomfort was measured using an 11-point (0–10) numerical rating scale (NRS), where 0 represents no discomfort and 10 represents the worst discomfort [25] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Small differences in MF slope in this study revealed that cross-legged floor sitting posture in handicraft work can be fatiguing to lower trunk muscles and cause low back discomfort over time. 13 Although there have been reports comparing laparoscopy to open surgery, or comparing performance between SILS and laparoscopy, our study is one of the first to compare muscle fatigue and mental workload in SILS and standard laparoscopy. Additionally, several previous ergonomic papers using sEMG and frequency analysis might have had methodological problems.…”
Section: Surgical Innovationmentioning
confidence: 91%
“…After that, pairs of active disc disposable Ag/AgCl surface electrodes (EL 503) with electrical contact surface areas of 1 cm 2 and a center-to-center spacing of 2.5 cm were attached parallel to each muscle on the right side as previously reported: TrA & IO muscle 19) , RA muscle 20) , LM muscle 21) and ICLT muscle 22) . The two ground electrodes of the right RA and ICLT muscles were placed over the ribcage and the other two ground electrodes of the right TrA & IO and LM muscles were placed over the right iliac crest.…”
Section: Methodsmentioning
confidence: 99%